2021
DOI: 10.46666/2021-4.2708-9991.02
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural sector of the Republic of Kazakhstan in terms of a pandemic

Abstract: The goal is to analyze the current state of agricultural sector in Kazakhstan, identify problems and develop proposals for its development in a pandemic. Methods - a systematic approach, functional, collection and generalization of facts, statistical and economic. Results - features of the functioning of agricultural market of the republic in terms of COVID-19 were considered. Actual data of the impact of the global pandemic on the volume of agricultural production, level of prices, the amount of demand for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Temirbekova A.B., Dulambayeva R.T., Kaldiyarov D.A., considered in their research the analysis of the current state of the agricultural sector in Kazakhstan, identify problems, and develop proposals for its development during the COVID-19 pandemic. Their article suggested that attention should be paid to producing high-quality organic food and expanding competition on the agri-food market through cooperative trade and distribution using digital platforms as an alternative to large retail chains [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Temirbekova A.B., Dulambayeva R.T., Kaldiyarov D.A., considered in their research the analysis of the current state of the agricultural sector in Kazakhstan, identify problems, and develop proposals for its development during the COVID-19 pandemic. Their article suggested that attention should be paid to producing high-quality organic food and expanding competition on the agri-food market through cooperative trade and distribution using digital platforms as an alternative to large retail chains [20].…”
Section: Literature Reviewmentioning
confidence: 99%